Strategies to Retain Loyalty Through Customer Satisfaction in East Java - Muchtolifah Muchtolifah; Aldila Ramadhani (Journal of Economics, Business, and Government Challenges, 2022)
Strategies to Retain Loyalty Through Customer Satisfaction in East Java